2012
DOI: 10.5433/1679-0359.2012v33n6p2423
|View full text |Cite
|
Sign up to set email alerts
|

Frequência alimentar no crescimento de alevinos de peixe-rei Odontesthes humensis

Abstract: ResumoA excelente qualidade da carne, a alta taxa reprodutiva e o amplo espectro alimentar sugerem grande potencial para cultivo do peixe-rei. Estudos relacionados à nutrição e alimentação são fundamentais para viabilizar o cultivo de espécies nativas e proporcionar o rápido e eficiente consumo do alimento e reduzir o desperdício de nutrientes. O objetivo deste trabalho foi avaliar a melhor frequência de suprimento de alimento para o crescimento do peixe-rei Odontesthes humensis. Para tal, 600 alevinos com pes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…) and can better enable the cultivation of the specie. However, normally, fish in the early stages have a high metabolic rate (Pouey, Rocha, Tavares, Portelinha & Piedras ), small stomach and gut, showing better growth when fed a higher daily rate. Probably, in this study, the amount provided for Artemia larvae twice daily was enough to meet the nutritional requirements of the species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…) and can better enable the cultivation of the specie. However, normally, fish in the early stages have a high metabolic rate (Pouey, Rocha, Tavares, Portelinha & Piedras ), small stomach and gut, showing better growth when fed a higher daily rate. Probably, in this study, the amount provided for Artemia larvae twice daily was enough to meet the nutritional requirements of the species.…”
Section: Resultsmentioning
confidence: 99%
“…This result is relevant for the cultivation of Pyrrhulina, since a reduced number of feeds results in greater savings in manpower, an item that accounts for a large proportion of the fixed production costs (Hayashi et al 2004) and can better enable the cultivation of the specie. However, normally, fish in the early stages have a high metabolic rate (Pouey, Rocha, Tavares, Portelinha & Piedras 2012), small stomach and gut, showing better growth when fed a higher daily rate. Probably, in this study, the amount provided for Artemia larvae twice daily was enough to meet the nutritional requirements of the species.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the congeneric Odontesthes humensis receives little attention from researchers and fish farmers. Only studies involving fry growth ( Pouey et al, 2012 ), embryos salinity tolerance ( Piedras et al, 2009 ), growth in intensive system ( Tavares et al, 2014 ), and toxicology ( Zebral et al, 2017 ) are developed in captivity specimens. Both O. bonariensis and O. humensis species have similar habitats, biological characteristics (including morphology), and are capable of interbreeding.…”
Section: Introductionmentioning
confidence: 99%
“…Santos et al (2015) reported that the dynamic of endogenous utilization of energy reflects in the use of lipids and products formed through cellular stock, in both absorption and use in metabolic demand. The possible alterations related to increased feeding frequencies suggest that fish use food as a priority in order to meet the energetic demands of body maintenance and reposition of catabolized tissues, which may still be directed to growth (Pouey et al, 2012;Ribeiro et al, 2012;Zhao et al, 2016). In this sense, the somatic index suggests the use of energetic reserves.…”
Section: Growth Performancementioning
confidence: 99%
“…Providing information about productivity and physiology of fish during food restriction can generate relevant information regarding the applicability of food managements in distinct production systems. In this sense, the dietary frequency in fish rearing might influence the levels of protein, cholesterol and triglycerides in plasmatic metabolism (Dieterich et al, 2013), as well as batch uniformity (Pouey et al, 2012), growth (Santos et al, 2014), and body composition with alterations in content moisture, protein, lipid and ash (Daudpota et al, 2016). Productive performance parameters (e.g.…”
Section: Introductionmentioning
confidence: 99%